2004
DOI: 10.1016/j.ydbio.2003.12.027
|View full text |Cite
|
Sign up to set email alerts
|

How cells dedifferentiate: a lesson from plants

Abstract: The remarkable regenerative capacity displayed by plants and various vertebrates, such as amphibians, is largely based on the capability of somatic cells to undergo dedifferentiation. In this process, mature cells reverse their state of differentiation and acquire pluripotentiality--a process preceding not only reentry into the cell cycle but also a commitment for cell death or trans- or redifferentiation. Recent studies provide a new perspective on cellular dedifferentiation, establishing chromatin reorganiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 66 publications
3
106
0
1
Order By: Relevance
“…These data demonstrate that AtS6K1 may up-regulate the expression of genes for cell cycle progression under different developmental and/or physiological conditions, such as in protoplasts, which are devoid of the cell wall structural components and undergoing the procedure of reestablishing cell fate determination (Grafi, 2004) although it was suggested that AtS6K1 may act as a repressor of cell proliferation (Henriques et al, 2010), which were also supported in our experimental data described above. However, CDKB1;1 transcript level in the auxin-treated protoplasts from transgenic line expressing HAAtS6K1 was less than that in auxin-treated protoplasts from untransformed Columbia (Fig.…”
Section: A B C E D Fsupporting
confidence: 83%
“…These data demonstrate that AtS6K1 may up-regulate the expression of genes for cell cycle progression under different developmental and/or physiological conditions, such as in protoplasts, which are devoid of the cell wall structural components and undergoing the procedure of reestablishing cell fate determination (Grafi, 2004) although it was suggested that AtS6K1 may act as a repressor of cell proliferation (Henriques et al, 2010), which were also supported in our experimental data described above. However, CDKB1;1 transcript level in the auxin-treated protoplasts from transgenic line expressing HAAtS6K1 was less than that in auxin-treated protoplasts from untransformed Columbia (Fig.…”
Section: A B C E D Fsupporting
confidence: 83%
“…Resetting of epigenetic information mechanistically underlies also the processes of cell fate switch, regeneration and regaining of pluripotency, and hence it is intriguing to investigate the possible parallels between these processes and the molecular hallmarks of the germline reprogramming. Extensive chromatin remodelling and heterochromatin decondensation have been observed in somatic cell nuclear transfer as well as during protoplast formation in plants and is one of the first observable features of the ongoing reprogramming process in both systems [42][43][44]. Changes in H3K9me as well as release of heterochromatin protein 1 (HP1) from chromatin observed during germline reprogramming have also been associated with the protoplast formation [43,44].…”
Section: Mechanistic Links To Other Reprogramming Systemsmentioning
confidence: 99%
“…Acquisition of the new fate requires an extensive reprogramming of gene expression and is accompanied by changes in chromatin structure (Grafi, 2004). Most studies on the dedifferentiation process have been carried out in a protoplast system.…”
Section: Dedifferentiationmentioning
confidence: 99%